Swear Word Used in Animated Situational Comedy Family Guy, Season 15, Episode 15 and 17 - Frina Diniarta Nur (ESENSI LINGUA, 2023)
This research aims at analyzing swear words found in animated situational comedy Family Guy, Season 15, Episode 15 and 17. The study aims to answer three research questions, i.e., the kinds of swear words, the reasons of using swear words, and the speaker-listener relation that elicits swear words. The theories used in analyzing the data are the theory of Michael Swan (1995) and Andrew Gray (2000). This study uses descriptive qualitative method. Thirteen data that contained swear words were found. Of these data, six kinds of swear words were found. They were exclamation of surprise, exclamation of annoyance, surprised question, insult, rejection, and intensifying adjective. There were two reasons that made the characters use swear words, i.e., to identify certain social class and to express emotion. However, the speaker-listener relation that made the speakers use swear words varied between relatives, friends, and strangers. Keywords: swear word, animated sitcom, Family Guy